Desenvolvimento radicular de soja em solo compactado - Trento, Sabrina de Matos (2014)
The traffic of heavy machinery in agriculture has caused superficial soil compaction. It is known that the soil can be chemically good, but if your physical structure to provide the conditions necessary for good root development the absorption of water and nutrients may be impaired. So with this work aimed to evaluate the root development of soybean in a compacted soil, with sowing in two furrowers mechanisms. Treatments consisted of two mechanisms furrow (double disc and shank) of a planter in soil-tillage with additional compression. The design was a randomized block with four replications, totaling eight experimental units. Through the Safira program were evaluated, surface area, volume, diameter and length of roots in 0-0,10, 0,10-0,20 and 0,20-0,30 m between rows and the row. Treatments stem and disc undergo further compaction had no effect on root development. There was no significant difference for any of the treatments in any of the studied depths.